Aerobic Transition‐Metal‐Free Synthesis of 2, 3‐Diarylindoles and 5‐Aryluracils via Oxidative Nucleophilic Substitution of Hydrogen Pathway. (23rd December 2015) - Yu, Jin; Moon, Hye Ran; Kim, Su Yeon; Kim, Jae Nyoung
Abstract :